To a critical situationism (Nóema, 2014)
Jean-Paul Sartre's philosophy, in L'être et le néant and in Critique de la raison dialectique, still maintains its validity as a reflection on our located liberty. However, we must criticize - in both senses of limiting it and correct it - on two points: 1) Sartre’s interpretation of matter and natural sciences seems like the interpretation given by logical positivists (Wienerkreis et al.); 2) social relations, analyzed by Sartre in a deep and convincing way, neglect or ignore more fundamental and anonymous social relations, which are necessary to account. The contributions of the neo-Kantian Marburg school, particularly those of Ernest Cassirer, can rectify the Sartrean philosophy, turning it into a critical situationism.
Keywords: Project; Facticity; Relationship; Freedom; Alienation; Unveiling; Constitution; Practical-inert field; transcendental logic; anonymous social relations